The The Association of Self-Perceived Eating Acculturation on Fatigue or Depressive Symptoms among Migrant Indonesian Women in Taiwan with Mental/Physical Distress History (Proceedings of the International Conference on Public Health, 2019)
Abstract: Migrant workers have been associated with increased vulnerability to fatigue and depression. However, it remains unknown whether self-perceived acculturation among women migrant workers (WMWs) affects fatigue and depressive symptoms in relation to mental/physical distress (MPD) history. Methods and Study Design:  235 Indonesian women migrants aged 20–50 years who were working in Taipei were studied. Self-perceived acculturation, dietary acculturation, body mass index, hemoglobin, fatigue and depressive symptoms were assessed. Results: The prevalence of fatigue or depressive symptoms was 40.8%. WMWs with MPD history are increased risk for fatigue (OR: 5.584 (2.694-11.574)) and depression (OR: 2.625 (1.242-5.549)) and they acculturate differently than women without MPD history. Among women with MPD history, a better self-perceived eating habit was associated with lower risk (OR: 0.132 (0.018 – 0.980)) for fatigue or depressive symptoms compared with no changes. Conclusion: a better self-perceived eating habit may protect women migrant with MPD history on fatigue or depressive symptoms
Keywords: Self-perceived eating, Acculturation, Fatigue, Depressive, Indonesian Female Migrant Workers